2020
DOI: 10.1111/jan.14669
|View full text |Cite
|
Sign up to set email alerts
|

The factors related to a sedentary lifestyle: A meta‐analysis review

Abstract: Aims To compare factors associated with the sedentary lifestyle described in the literature with the factors listed in NANDA International. Design Systematic review with meta‐analysis of factors associated with a sedentary lifestyle in adolescents, adults and older people. Data sources An electronic search of PubMed, Scopus, CINAHL and Latin America and the Caribbean Literature on Health and Science databases conducted in May 2016. Review methods Descriptive data were extracted according to a standardized form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 71 publications
1
38
0
14
Order By: Relevance
“…In addition, Martins et al, (2021) also identified other factors considered possibly important for the occurrence of sedentary lifestyle, such as "Education in a public institution," "Education level" and "Marital status (having a partner)," although these factors did not present significance in the meta-analysis. Considering the authors' recommendations, the present study includes these factors so that they could be tested in the target population (adult patients with arterial hypertension).…”
Section: Backg Rou N Dmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, Martins et al, (2021) also identified other factors considered possibly important for the occurrence of sedentary lifestyle, such as "Education in a public institution," "Education level" and "Marital status (having a partner)," although these factors did not present significance in the meta-analysis. Considering the authors' recommendations, the present study includes these factors so that they could be tested in the target population (adult patients with arterial hypertension).…”
Section: Backg Rou N Dmentioning
confidence: 98%
“…No additional factors from the literature were investigated. In contrast, other studies (Martins et al, 2015(Martins et al, , 2021 have found new aetiological factors for SL; however, such elements need to be evaluated clinically in a specific population to generate more robust clinical evidence. From this perspective, there is a need to validate the related factors of SL in individuals with arterial hypertension to obtain sufficient evidence about the strength of the relationship between these factors and the diagnosis.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations